A comparative study on the effectiveness of tabular method and traditional method in solving problems involving integration by parts - Billones, Katrina A.; Bucago, Alyanna Mari T.; Reyes, Ken, Romero, Davie Jane F. and Salandanan, Hester Joy E. 4 0 16; 5
u
Research Paper: (Bachelor of Science in Mathematics) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2